Analysis of Anti-Jamming Performance of HF Access Network Based on Asymmetric Frequency Hopping - Ruijie Duan; Liang Jin; Xiaofei Lan (Sensors)
The primary focus of this paper lies in addressing the inadequate anti-dynamic jamming capability of the link layer within high-frequency (HF) access networks. To this end, we propose the incorporation of asymmetric frequency-hopping (AFH) technology within the wireless communication segment of HF access networks. This innovation aims to supersede the existing fixed-frequency and frequency-hopping communication methodologies, ultimately enhancing the network’s resilience against dynamic jamming. Moreover, we undertake a modeling analysis to delve into the ramifications of asymmetric frequency-hopping communication in dynamic jamming environments. This modeling framework serves to elucidate the dynamics of user spectrum occupation and jamming occurrences. Our proposed methodology leverages a two-dimensional Markov queuing model, equipped with a single server, for the purpose of managing the spectrum allocation within HF access network subnets. Consequently, the base station gains the capability to dynamically manage and adjust the available spectrum in real time, thereby effectively mitigating mutual jamming among users and facilitating the seamless implementation of asymmetric frequency hopping in HF access networks. Lastly, we conduct a simulation analysis to evaluate the changes in anti-jamming performance indices within the HF access network. This analysis compares the merits and demerits of utilizing fixed-frequency, frequency-hopping, and asymmetric frequency-hopping communication techniques. Our findings conclusively demonstrate that the integration of asymmetric frequency-hopping technology can significantly reduce outage and mutual jamming rates within HF access network subnets, thereby substantially bolstering their anti-jamming prowess.